+0  
 
-5
240
1
avatar+956 

Rewrite in simplest radical form:

 Apr 5, 2019
 #1
avatar+111392 
0

First one.....convert to exponential form....

 

(50r^2s^4)^(1/2)  =   ( 25 * 2 * r^2 * s^4)  =  (25)^(1/2) * (2)^(1/2) * (r^2)^(1/2) * (s^4)^(1/2) =

 

5 * (2)^(1/2) * r * s^2  =

 

5 r s^2 √2

 

 

Second one      3 √[18x^3]  =  3  √ [ 9 * 2 * x^3 ]  =   3 *(9)^(1/2) * (2)^(1/2) * (x^2)^(1/2) * (x)^(1/2)  =

 

3 * 3 * 2^(1/2) * x * (x)^(1/2)  =

 

9 * x * 2^(1/2) * (x)^(1/2)  =

 

9x  √ [ 2x ]

 

cool cool cool

 Apr 5, 2019

28 Online Users

avatar